(untitled) (CIPEEX, 2022)
OBSTETRIC VIOLENCE (OV) IS UNDERSTOOD AS ALL PHYSICAL, MORAL, PROPERTY OR PSYCHOLOGICAL VIOLENCE EXPERIENCED BY A PARTURIENT WOMAN IN CHILDBIRTH, POSTPARTUM AND PUERPERIUM. IN THE MEANTIME, THIS INTEGRATIVE REVIEW WAS DESIGNED TO IDENTIFY THE FACTORS ASSOCIATED, IN THE SCIENTIFIC LITERATURE, WITH THE PERSISTENCE OF OBSTETRIC VIOLENCE IN BRAZIL. IT AIMS TO DESCRIBE THE FACTORS ASSOCIATED IN DIFFERENT SOCIAL SPHERES AND THE DIFFICULTY ENCOUNTERED BY WOMEN IN RECOGNIZING THIS TYPE OF VIOLENCE. WE USED FOURTEEN ORIGINAL ARTICLES THAT ANSWER THE GUIDING QUESTION OF THIS STUDY: "WHAT ARE THE FACTORS ASSOCIATED WITH THE PERSISTENCE OF OBSTETRIC VIOLENCE IN BRAZIL? THESE ARTICLES WERE FOUND IN THE LATIN AMERICAN AND CARIBBEAN LITERATURE ON HEALTH SCIENCES (LILACS), NURSING DATABASE (BDENF) AND MEDICAL LITERATURE ANALYSIS AND RETRIEVAL SYSTEM ONLINE (MEDLINE) DATABASES, USING THE FOLLOWING HEALTH DESCRIPTORS: "OBSTETRIC VIOLENCE", "PARTURITION" AND "BRAZIL", AS WELL AS SYNONYMS, WHICH WERE COMBINED WITH THE BOOLEAN OPERATOR "AND". IT WAS FOUND THAT THE REVIEWED STUDIES POINTED OUT THAT EACH EXPERIENCE OF CHILDBIRTH, POSTPARTUM AND PUERPERIUM IS PARTICULAR, BUT THAT THERE ARE FACTORS THAT ASSOCIATE THIS EXPERIENCE TO A LIVED VIOLENCE, BEING THEM PERSONAL, INTERPERSONAL, INSTITUTIONAL AND ASSISTANCE. OF THE REVIEWED ARTICLES, THAT THE WOMEN PARTICIPATING IN THE STUDIES REPORTED THEIR EXPERIENCES AS PARTURIENTS SUFFERED DIFFERENT TYPES OF OBSTETRIC VIOLENCE. IT IS CONCLUDED THAT FROM THE ARTICLES REVIEWED, THE WOMEN PARTICIPATING IN THE STUDIES REPORTED THEIR EXPERIENCES AS PARTURIENTS SUFFERED DIFFERENT TYPES OF OBSTETRIC VIOLENCE, BEING NECESSARY THE REALIZATION OF FURTHER STUDIES, IN ORDER TO CLARIFY IN A MORE SOLID WAY THE PERSISTENCE OF THESE REPORTS OF VO IN BRAZIL.